DOI: 10.18174/403639
|View full text |Cite
|
Sign up to set email alerts
|

First week nutrition for broiler chickens : effects on growth, metabolic status, organ development, and carcass composition

Abstract: During the first week of life, broiler chickens undergo various developmental changes that are already initiated during incubation. Ongoing development of organs such as the gastrointestinal tract and the immune system may affect the nutritional requirements during this age period. Despite the residual yolk that is available at hatch and that may provide nutritional support during the first days after hatch, the growth performance may be affected by the time in between hatch and first feed intake. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
(171 reference statements)
0
4
0
Order By: Relevance
“…The present model was able to induce gut leakage in young (14-day-old) broiler chickens, and it was not acute enough to affect older (28-day-old) chickens. Such a compensatory mechanism was previously demonstrated in broiler chickens (Maiorka et al, 2003;Santos et al, 2021) and might be an adaptive gut response after exposure to diverse sources of stress or dietary challenges (Lamot 2017). It is important to bear in mind that mRNA expression will not necessarily reflect the actual protein expression in tissue.…”
Section: Resultsmentioning
confidence: 95%
“…The present model was able to induce gut leakage in young (14-day-old) broiler chickens, and it was not acute enough to affect older (28-day-old) chickens. Such a compensatory mechanism was previously demonstrated in broiler chickens (Maiorka et al, 2003;Santos et al, 2021) and might be an adaptive gut response after exposure to diverse sources of stress or dietary challenges (Lamot 2017). It is important to bear in mind that mRNA expression will not necessarily reflect the actual protein expression in tissue.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, in previous studies conducted on older birds, it was reported that there is a correlation between increasing energy density and decreased FI (10,23). According to Lemot et al (1), if the diet's energy density increases during the first week of a chick's life, the bird's ability to assimilate the nutrients in the food may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…roiler chickens require a pre-starter diet during their first week of life to support growth and development due to their immature digestive system (1,2). Manipulating this diet can modify chicken development (3), but there is limited information on the effects of early nutrition and the composition of the pre-starter diet.…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors [8,9] have suggested that other factors in combination with genetic make-up, such as nutrition, environment, age, sex, management, and health care, account for the successes achieved in managing dietary energy intake of broilers. Modern broilers perhaps eat to their physical capacity or adjust their feed intake in response to several factors including dietary energy [10], and increased nutrient density results in a linear improvement in weight gain and feed efficiency, without reduction in intake [11]. According to [12] constant intake of feeds high in protein and other nutrients increases supply of energy and results in a linear increase in protein accretion in tissues, until a maximum rate -a genetically defined term, is reached.…”
Section: Introductionmentioning
confidence: 99%